Media, Power and Empowerment : Central and Eastern European Communication and Media Conference CEECOM Prague 2012. - Reifová, Irena (Cambridge Scholars Publishing, 2014)
This collection brings together 71 papers by 83 authors from 20 countries presented at the 5th Central and Eastern European Communication and Media Conference, titled ""Media, Power and Empowerment"", in Prague, Czech Republic, in April 2012. It maps out trends in CEE media research across the entire region and provides insight into the broad span of relevant topics. The contributors to the volume successfully voice the multiple, yet specific, questions relevant to the CEE countries; the papers ...